The Influence of Corporate Governance Mechanism on the Relationship between Related Party Transactions and Earnings Management - Mita, Aria Farah; Utama, Sidharta (Universitas Prasetiya Mulya, 2014)
The objective of this study is to investigate the relationship between related party transactions (RPT) and earnings management. This study argues there is a different influence between RPT a priori likely to result in expropriation and RPT a priori not likely to result in expropriation. RPT a priori likely to result in expropriation creates an incentive to management or controlling shareholder to overstate income to cover or mask their expropriation. This study uses non-absolute discretionary accruals based on Kazsnik model to proxy earnings management. Corporate governance mechanism should reduce the incentive to overstate income in a company that involves in RPT a priori likely to result in expropriation. The results of this study show that the earnings management (income increasing) is affected by the existence of RPT a priori likely to result in expropriation and corporate governance mechanism, but it is not affected by the size/value of the transactions. As expected, companies involving in RPT a priori likely to result in expropriation with weak corporate governance mechanism, tend to manage earnings that increase income. We find that strong corporate governance mechanism decreases the discretionary accruals in companies which have RPT a priori likely to result in expropriation.